Lightweight and compressible anisotropic honeycomb-like graphene composites for highly tunable electromagnetic shielding with multiple functions. (May 2022) - Chen, Jiali; Shen, Bin; Jia, Xichen; Liu, Yinfeng; Zheng, Wenge
Abstract: Lightweight and highly compressible macrocellular honeycomb-like graphene composites with anisotropic structure are fabricated by orderly assembling hollow porous macrotubes of reduced graphene oxide into an array structure and encapsulating them with polydimethylsiloxane. The architecture could not only show high comprehensive electromagnetic interference (EMI) shielding performance up to ∼14524 dB cm 2 g −1, but also tune the shielding effectiveness (SE) (or R/A ratio) through adjusting either orientation direction or compressive strain, thus exhibiting broadened SE and R/A tuning range by integrating the two SE-tuning modes, which exceeds that of most reported lightweight porous EMI shields with tunable performance. Besides, it further possesses excellent piezoresistive sensing capability as well as outstanding anisotropic thermal-insulation and low-voltage-driven Joule-heating functions, which can provide the ability to detect the physical impact and minimize the impact of extreme environments on electronic equipments during effective EMI shielding. The satisfactory performance of such architecture confirms that macrocellular structural design of nanomaterials is an effective way to develop high-performance and multifunctional EMI shields with convenient performance regulation. Graphical abstract: Image 1 Highlights: Highly compressible anisotropic honeycomb-like graphene composites with high EMI-shielding performance are fabricated. The composites can realize convenient SE regulation through change in either orientation direction or compressive strain. The composites exhibit multiple functions, including piezoresistive sensing, thermal-insulation, and Joule-heating.